Exploration of ethnomathematics and the philosophical meaning of the Al-Abror Grand Mosque in Padangsidimpuan as a medium for delivering material on Solid Geometry - Anggi Indah Riskiyah Harahap; Eka Khairani Hasibuan (Desimal: Jurnal Matematika, 2025)
This study investigates the three-dimensional geometric concepts and the underlying philosophical meanings embodied in the architecture of the Great Mosque of Al-Abror, Padangsidimpuan, employing a qualitative approach with ethnographic methods. The research is motivated by a notable gap in ethnomathematics scholarship, which has predominantly focused on identifying geometric forms without thoroughly integrating the associated philosophical and Islamic cultural values. Data were collected through direct observation, interviews with mosque administrators, and visual documentation, complemented by an extensive literature review. Data analysis was conducted using Miles and Huberman’s interactive model, encompassing data reduction, data display, and reflective conclusion drawing. The findings reveal that the mosque’s architecture incorporates a variety of three-dimensional geometric forms, including cubes, rectangular prisms, pyramids, cylinders, and spheres, which serve not only structural functions but also convey rich symbolic meanings, such as unity, steadfast faith, balance, and order in alignment with Islamic teachings. This integration of geometric analysis and philosophical interpretation offers a more contextualized understanding of mathematics and simultaneously fosters the internalization of cultural and religious values among learners. The novelty of this research lies in its comprehensive integration of geometric exploration with philosophical interpretation in the study of mosque architecture. Future research is encouraged to broaden the scope to other historical structures, develop technology-enhanced learning media, and evaluate their effectiveness in improving students’ academic performance and cultural appreciation.